Tinea pseudoimbricata as a unique manifestation of steroid abuse: A clinico-mycological and dermoscopic study from a tertiary care hospital - Archana Singal; Deepak Jakhar; Ishmeet Kaur; Deepika Pandhi; Shukla Das (Wolters Kluwer Medknow Publications, 2019)
Background: Tinea pseudoimbricata, characterized by concentric scaly rings simulating Tinea imbricata is caused by dermatophytes other than Trichophyton concentricum. It is reported to occur in patients with steroid abuse and in immunocompromised individuals. Aim: To study the clinico-mycological profile and dermoscopic features of T. pseudoimbricata in immunocompetent patients. Methods: We have evaluated 14 consecutive, clinically diagnosed patients of T. pseudoimbricata with positive 10% potassium hydroxide (KOH) examination and culture, seen over a period of 6 months. Dermoscopy was performed in all patients. The demographic, clinical, and mycological features of each patient were recorded on a predesigned proforma. Results: There were seven male and seven female patients with a mean age of 27.6 years and a mean disease duration of 3.8 months. All patients gave a history of application of potent or super-potent topical steroid with or without oral/injectable steroid for varying duration. Culture isolates were Trichophyton mentagrophytes complex and Trichophyton rubrum in 11 and 3 patients, respectively. Dermoscopic analysis showed features of steroid abuse in majority of the patients. Limitation: A small sample size was the limitation of our study. Conclusion: T. pseudoimbricata is a special subset of Tinea incognito caused by injudicious and inappropriate use of topical steroid. The typical appearance should alert the dermatologists regarding the possible abuse of steroids. Most common species isolated on culture was T. mentagrophytes complex.